2020
DOI: 10.2138/am-2020-6972
|View full text |Cite
|
Sign up to set email alerts
|

Hornblende as a tool for assessing mineral-melt equilibrium and recognition of crystal accumulation

Abstract: Bulk-rock compositions are commonly used as proxies for melt compositions, particularly in silicic plutonic systems. However, crystal accumulation and/or melt loss may play an important role in bulk-rock compositional variability (McCarthy and Hasty 1976; McCarthy and Groves 1979; Wiebe 1993; Wiebe et al. 2002; Collins et al. 2006; Deering and Bachmann 2010; Miller et al. 2011; Vernon and Collins 2011; Lee and Morton 2015; Lee et al. 2015; Barnes et al. 2016a; Schaen et al. 2018). Recognizing and quantifying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 75 publications
5
16
0
Order By: Relevance
“…It is noteworthy that the phase assemblages from rhyolite-MELTS modelling here should be treated with caution because rhyolite-MELTS cannot easily deal with amphibole crystallization (Ghiorso and Sack 1995;Gualda et al 2012). However, the situation that amphibole crystallizes from more evolved melts than the bulk-rock composition of the host is consistent with general observations in plutonic rocks (e.g., Werts et al, 2020), as well as the observed coexistence of amphibole and quartz within some glomerocrysts in this study ( Fig. 4a; Supplemental Fig.…”
Section: Evolution Of the Narusongduo Magmatic Systemsupporting
confidence: 89%
“…It is noteworthy that the phase assemblages from rhyolite-MELTS modelling here should be treated with caution because rhyolite-MELTS cannot easily deal with amphibole crystallization (Ghiorso and Sack 1995;Gualda et al 2012). However, the situation that amphibole crystallizes from more evolved melts than the bulk-rock composition of the host is consistent with general observations in plutonic rocks (e.g., Werts et al, 2020), as well as the observed coexistence of amphibole and quartz within some glomerocrysts in this study ( Fig. 4a; Supplemental Fig.…”
Section: Evolution Of the Narusongduo Magmatic Systemsupporting
confidence: 89%
“…TIC rocks are metaluminous to locally peraluminous, calcalkaline compositions, spanning a wide range of SiO 2 contents (48-79 wt.%) (Bateman and Chappell, 1979;Bateman, 1992;Memeti et al, 2014). Hornblende analyses indicate that all units experienced crystal accumulation and/or melt loss to varying degrees, contributing to the wide variation in rock type (Barnes et al, 2016;Werts et al, 2020). The considerable compositional overlap between units in major and trace elements, as well as isotopes, has been attributed to a combination of fractionation and mixing processes involving multiple magma sources; the depth that these processes occur is debated (e.g., Kistler et al, 1986;Bateman, 1992;Gray et al, 2008;Coleman et al, 2012;Memeti et al, 2014;Barnes et al, 2016).…”
Section: The Tuolumne Intrusive Complexmentioning
confidence: 99%
“…We used these intersections to estimate the bulk composition of a TIC magma that we could model under fixed pressure and varying temperature conditions. Werts et al (2020) and Barnes et al (2020), using the thermometer of Putirka (2016), calculated hornblende crystallization temperatures ranging from >800 to ∼650 • C across all TIC units. As hornblende is abundant in all schlieren studied, the temperature range 800-700 • C was considered relevant to schlieren formation to a first order.…”
Section: Relative Timing Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcic amphibole is an important constituent of basic to acid metaluminous igneous rocks and their metamorphic derivatives (e.g., Robinson et al, 1982;Wones and Gilbert, 1982;Martin, 2007;Schumacher, 2007). Many studies have been devoted to determine its P-T-X relationships in both synthetic and natural assemblages (e.g., Czamanske and Wones, 1973;Laird and Albee, 1981;Thompson et al, 1982;Apted and Liou, 1983;Poli, 1993;Spear, 1993;Poli, 1998, 2000;García-Casco et al, 2008;Molina et al, 2009;Bucher and Grapes, 2011;Castro, 2013;Werts et al, 2020). These studies have provided a basis for the calibration of numerous thermometers and barometers that make it possible to determine the P-T conditions of crystallization/re-equilibration of amphibole-bearing assemblages.…”
Section: Introductionmentioning
confidence: 99%